Web-based Business Management System for SSK Surprise Delivery - Murugan, Lugeshwar; Munirah Yusof, (Applied Information Technology And Computer Science, 2022)
Being a newly established business, SSK Surprise Delivery is facing difficulties to get exposure among customers due to other well-known businesses. In addition, SSK Surprise Delivery faces challenges in retrieving orders and recording the sales report manually. Hence, a web-based business management system is developed to help him to manage his business. The system is developed with a linear and sequential approach utilizing the classical waterfall model. Upon completion of the system development, the system will have login module, registration module, product module, and tracking module. The system also developed to generate the sales report automatically to ease the recording of the transactions. In conclusion, this system ensures that the owner can manage and develop his business from anywhere and at any time just by accessing the system. In future, the system could be upgraded to application which will avoid the necessary to access the system from browsers.